"Korean wave" in the dialectic of cultural development - V.S. Grytsenko, (Ukrainian Cultural Studies, 2020)
The article covers the consideration of the "Korean Wave" as one of the manifestations of dialectical laws of culture development. The interpretation of the phenomenon only as a situational model of state cultural policy is refuted through the analysis as an incorrect and unreasonably narrowed understanding. We consider the "Korean Wave"as a variant of the cultural wave, which is a constant element in general processes of cultural development of mankind; we substantiate the grounds for its studying from the point of view of dialectical unity of internal and external factors. We show that the features of its formation and functioning determined by this way have expert ability in the analysis of the processes of culture creation, which are extremely accelerated today.In this connection, essential comprehension of the culture as living organism, caused by spiritual and generic motivations of a man and connected with his continuous self-development, displays its principality. In this sense, the "Korean Wave",a phenomenon of modern stage of culture development, shows itself as its regular stage, connected with its dynamicmorphological features. It displays an example of the cultural wave as a component of general cultural cyclicality, caused by permanent motionfraught with excitationand wavyoutbursts. Every such wave, having its historically specific motivation, is transparent regarding general mechanisms of cultural development.The absence of direct studies of culture dialectics, one component of which is shown by the phenomenon of the cultural wave, is the cause of dominating in modern culture studies of a descriptive factology principle. From the position of understanding the dialectics of general cultural movement, the appearance of a new one, the"Korean Wave"in this case, is a result of complicated multistage processes happening in the public culture body, where quantity is transformed into quality, trends into laws in response to spiritual needs of a man. It completely concerns the "Korean Wave"as well, as in collisions of its appearance, the complicated relations between the old and the new, tradition and situationality, closeness and openness, emotional and rational issues are involved.
Keywords: hallyu, "korean wave", "soft policy power", sociocultural transformations, cultural dynamics, cyclicality, cultural wave, soliton